Enhancing user authentication for cloud web-based application / Detar Beqo - Detar , Beqo (2018)
Together with the fast growth of networks and mobile devices, cloud computing has become one of the top technologies that everyone has been talking about in the last decade. At the same time, it has become one of the most attractive and effective business solutions for many companies worldwide. Organizations are gradually migrating their employees’ data into the cloud environments, due to flexibility and cost efficiency which the cloud systems offer. However, as organization are moving their data and employees’ information into the cloud, it has become a great challenge to design a secure cloud system, as it strongly lies on the chosen authentication, as it is the one which provides authenticity and confidentially respectively. Due to virtualization and multi-tenancy of the cloud systems, the complexity of security issues has even increased compared to traditional data centers, and in many instances user accounts have been compromised. As a result of these incidents in recent years, there is a growing lack of trust in cloud infrastructures. This thesis present research on cloud security challenges and how they can be addressed by enhancing the current authentication mechanism. Security requirements of SaaS environments differs from traditional data centers. To address a specific cloud security challenges, an enhanced authentication method is developed during this research work. Motivated by a number of security experts in cloud computing, we proposed an innovative solution of authentication for cloud web-based applications. We aim to improve on passwords with respect to both usability as well as security. It uses an enhanced encryption algorithm, and the data is stored securely in the cloud systems. The proposed authentication method, uses an enhanced method where the credentials are encrypted through an algorithm. As a result, the user’s information is more secured, and the risk of compromised accounts is less, compared with two factor authentication. We have developed a cloud-based application that adapts the enhanced authentication method, and its security measurement were evaluated using IBM Application Security on Cloud tool. Results of different security testings are then compared to validate the effectiveness of the proposed authentication method.